Application of UTBB (SOI)-S-BE Tunnel-FET as a Dual-Technology Transistor - Mori, Carlos A. B.; Agopian, Paula G. D. [UNESP]; Martino, Joao A.; IEEE (Ieee, 2019)
In this work we propose for the first time the use of the recently introduced UTBB (SOI)-S-BE TFET (Ultra-Thin Body and Box Back Enhanced Silicon-On-Insulator Tunnel-FET) operating as a MOSFET device only by changing its bias condition. The principle is based on the carrier type generated by the back gate electric field. For negative back gate and drain biases applied in the device studied in this work, it works like a pTFET, while for positive ones it operates as an nMOS. TCAD device simulation was used for the proof of concept.
Keywords: Silicon-On-Insulator (SOI); Tunnel-FET; MOSFET; Reconfigurable transistor; dual technology transistor